Caspase-9: A Multimodal Therapeutic Target With Diverse Cellular Expression in Human Disease - Avrutsky, Maria I.; Troy, Carol M. (Frontiers in Pharmacology, 2021)
Caspase-9, a cysteine-aspartic protease known for its role as an initiator of intrinsic apoptosis, regulates physiological cell death and pathological tissue degeneration. Its nonapoptotic functions, including regulation of cellular differentiation/maturation, innate immunity, mitochondrial homeostasis, and autophagy, reveal a multimodal landscape of caspase-9 functions in health and disease. Recent work has demonstrated that caspase-9 can drive neurovascular injury through nonapoptotic endothelial cell dysfunction. CASP9 polymorphisms have been linked with various cancers, neurological disorders, autoimmune pathologies and lumbar disc disease. Clinical reports suggest alterations in caspase-9 expression, activity or function may be associated with acute and chronic neurodegeneration, retinal neuropathy, slow-channel myasthenic syndrome, lumbar disc disease, cardiomyopathies, atherosclerosis and autoimmune disease. Healthy tissues maintain caspase-9 activity at low basal levels, rendering supraphysiological caspase-9 activation a tractable target for therapeutic interventions. Strategies for selective inhibition of caspase-9 include dominant negative caspase-9 mutants and pharmacological inhibitors derived from the XIAP protein, whose Bir3 domain is an endogenous highly selective caspase-9 inhibitor. However, the mechanistic implications of caspase-9 expression and activation remain indeterminate in many pathologies. By assembling clinical reports of caspase-9 genetics, signaling and cellular localization in human tissues, this review identifies gaps between experimental and clinical studies on caspase-9, and presents opportunities for further investigations to examine the consequences of caspase activity in human disease.